Pleiotropy drives evolutionary repair of the responsiveness of polarized cell growth to environmental cues - Kingma, Enzo; Diepeveen, Eveline T.; Iñigo de la Cruz, Leila; Laan, Liedewij (Frontiers in Microbiology, 2023)
The ability of cells to translate different extracellular cues into different intracellular responses is vital for their survival in unpredictable environments. In Saccharomyces cerevisiae, cell polarity is modulated in response to environmental signals which allows cells to adopt varying morphologies in different external conditions. The responsiveness of cell polarity to extracellular cues depends on the integration of the molecular network that regulates polarity establishment with networks that signal environmental changes. The coupling of molecular networks often leads to pleiotropic interactions that can make it difficult to determine whether the ability to respond to external signals emerges as an evolutionary response to environmental challenges or as a result of pleiotropic interactions between traits. Here, we study how the propensity of the polarity network of S. cerevisiae to evolve toward a state that is responsive to extracellular cues depends on the complexity of the environment. We show that the deletion of two genes, BEM3 and NRP1, disrupts the ability of the polarity network to respond to cues that signal the onset of the diauxic shift. By combining experimental evolution with whole-genome sequencing, we find that the restoration of the responsiveness to these cues correlates with mutations in genes involved in the sphingolipid synthesis pathway and that these mutations frequently settle in evolving populations irrespective of the complexity of the selective environment. We conclude that pleiotropic interactions make a significant contribution to the evolution of networks that are responsive to extracellular cues.